The Role of the UN Security Council in the Process of Securitization of World Cultural Heritage - Iu. V. Vorobyova (Проблемы постсоветского пространства, 2020)
The deliberate activity of terrorist groups to destroy cultural heritage sites triggered the securitization of World Cultural Heritage concept. Among the actors of the securitization process, the UN Security Council plays a special role as the main body responsible for ensuring and maintaining international peace and security. Within the framework of UN Security Council resolutions, the base was gradually prepared linking the destruction and plunder of World Cultural Heritage sites, the illicit trafficking of cultural property with the financing of terrorist activities. This process took place in line with the securitization process, increasingly linking the protection of cultural sites with the maintenance of international peace and security. The article assesses the impact the in activities of the UN Security Council on the process of securitization of the World Cultural Heritage and on the development of regional legislation in the field of protection of such heritage.